KULTUREL KOMPLEKSITET OG EMPIRI-BRICOLAGE: Refleksioner over et projekt om etniske minoritetsungdom og multikulturalisme - Mørck, Yvonne (Tidsskriftet Antropologi, 1995)
Yvonne Mørck: Cultural Complexity and Empirical Bricolage - Reflections on a Project on Ethnic Minority Youth and Multiculturalism The article draws on experiences from fieldwork among ethnic minority youths in the greater Copenhagen area as well as on studies in London. In order to do anthropological work in the complex and modem world, especially in urban spaces of the metropolis, the anthropologist needs more sophisticated methods and sources of information than conventional anthropology can produce. At the same time different theoretical perspectives should supplement one another. This implies that on the methodological/ empirical as well as on the theoretical level we need the model of „bricolage" in order to refine our analysis. The anthropologist should therefore be a „nomadic subject" with a „nomadic consciousness" as the advocated nomadism refers to a kind of critical consciousness that resists settling into socially coded modes of thought and behaviour.